Feasibility of Dual-Task Gait Training for Community-Dwelling Adults after Stroke: A Case Series - Prudence Plummer; Raymond M. Villalobos; Moira S. Vayda; Myriam Moser; Erin Johnson (Stroke Research and Treatment)
This case series explored the feasibility and efficacy of cognitive-motor dual-task gait training in community-dwelling adults within 12 months of stroke. A secondary aim was to assess transfer of training to different dual-task combinations. Seven male participants within 12 months of stroke participated in 12 sessions of dual-task gait training. We examined single and dual-task performance in four different dual-task combinations at baseline, after 6 and 12 sessions, and if possible, at 1-month followup. Feasibility was assessed by asking participants to rate mental and physical fatigue, perceived difficulty, anxiety, and fear of falling at the end of each session. Five of the seven participants demonstrated reduced dual-task cost in gait speed in at least one of the dual-task combinations after the intervention. Analysis of the patterns of interference in the gait and cognitive tasks suggested that the way in which the participants allocated their attention between the simultaneous tasks differed across tasks and, in many participants, changed over time. Dual-task gait training is safe and feasible within the first 12 months after stroke, and may improve dual-task walking speed. Individuals with a combination of physical and cognitive impairments may not be appropriate for dual-task gait training.